Effects of acetylcholinesterase inhibitors on cognitive function in patients with chronic traumatic brain injury : A Systematic Review - Nadia Afnani Er Rahmah; Tsalis Yuna Hafshoh; Ritsya Aulia Isnani; Zhaki Al Asror; Ahmad Zayyin Najah (The International Journal of Medical Science and Health Research, 2025)
Introduction: Chronic Traumatic Brain Injury (TBI) often results in persistent cognitive impairments due to the disruption of the cholinergic system. Acetylcholinesterase inhibitors (AChEIs) are investigated to counter this, but the evidence for their efficacy is inconsistent, necessitating a systematic review to synthesize the current evidence. Methods: Following PRISMA 2020 guidelines, a systematic search was conducted across databases including PubMed and Google Scholar. The review included randomized controlled trials (RCTs) and systematic reviews focused on AChEIs in adults with chronic TBI. Eight studies were included in the final synthesis. Results: The evidence revealed highly significant, agent-specific effects rather than a uniform class benefit. A meta-analysis identified a statistically significant and large effect size for donepezil on aggregated cognitive outcomes (d=1.68, p=0.03). Separately, galantamine produced a statistically significant improvement in episodic memory (p=0.011) in an RCT. In direct and significant contrast, a large, multi-center RCT found no significant difference between the rivastigmine patch and placebo on its primary verbal memory outcome (p=0.41). A significant safety finding from a large meta-analysis was an increased risk of syncope (relative risk 1.50) associated with cholinesterase inhibitors. Conclusion: The evidence indicates that the therapeutic benefit of AChEIs in chronic TBI is not universal, but drug-specific. The significant positive signals for donepezil and galantamine, contrasted with the strong evidence of non-efficacy for rivastigmine, highlight this disparity. The compelling but preliminary finding for donepezil warrants urgent replication in large-scale, dedicated RCTs to confirm its potential as an adjunct to comprehensive rehabilitation for TBI.